Changements d’horizon : Circa, une aventure éditoriale traversant les frontières - Valérie Morisson (Revue LISA)
From its creation, in 1981, to the present day, Circa art magazine has played a crucial role in the evolution of the visual arts in Ireland. It has contributed to disseminating contemporary aesthetic forms as well as postmodern theories, and has widened the scope of criticism. It has also fostered a vital interest in the international avant-garde which geared artists towards a better understanding of their role in society and a greater awareness of artistic experimentation. The magazine’s agenda does not shun political issues. Circa has favored cultural reconciliation with Great Britain and has set common goals for Northern Ireland and the Republic. It has initiated connections with other marginal countries. The authors have also repeatedly avoided the pitfalls of cultural nationalism and promoted a fruitful dialogue between the local and the global. The evolution of this magazine testifies to Ireland’s growing openness to foreign influences and its desire to be on a par with other European countries in terms of artistic endeavours.